2018
DOI: 10.1111/wrr.1
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive virtual reality for procedural pain management of burn patients during dressing change or physical therapy: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Dressing change and physical therapy are extremely painful procedures for burn patients. Adjunctive virtual reality therapy reportedly reduces pain when added to analgesics, but a summary analysis of the data has yet to be performed. We conducted this systematic review and meta‐analysis of randomized controlled trials to verify the pain‐reducing efficacy of virtual reality among burn patients undergoing dressing change or physical therapy. We searched MEDLINE (via PubMed), EMBASE (via OVID), and the Cochrane C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 45 publications
(100 reference statements)
2
29
0
2
Order By: Relevance
“…Effective pain management is crucial for colonoscopy patients because high levels of pain decrease colonoscopy completion rates and willingness to return for repeat colonoscopies 6 7 . Our findings corroborate other studies that point to VR as an effective anxiolytic and analgesic that does not compromise patient care or satisfaction 4 5 .…”
Section: Discussionsupporting
confidence: 91%
“…Effective pain management is crucial for colonoscopy patients because high levels of pain decrease colonoscopy completion rates and willingness to return for repeat colonoscopies 6 7 . Our findings corroborate other studies that point to VR as an effective anxiolytic and analgesic that does not compromise patient care or satisfaction 4 5 .…”
Section: Discussionsupporting
confidence: 91%
“…For example, VR experiences designed to assist burn victims often utilize visual scenes that include cold weather and snow, taking advantage of the brain's tendency to respond physiologically to environmental cues. A recent review of research examining VR for pain management in burn victims concluded that the addition of VR to dressing change or physical therapy sessions significantly reduced pain intensity, time spent thinking about pain, and unpleasantness [10]. The current study adds to the accumulating evidence that VR has the potential to make basic medical procedures, such as a blood draw, much more tolerable, potentially improving patient compliance and willingness to donate blood [11].…”
Section: Discussionmentioning
confidence: 81%
“…Functional magnetic resonance imaging of the brain reveals that VR has similar effects on the sensory and insular cortex as opioids, and head-to-head trials show that VR achieves similar or greater analgesia as hydromorphone. [6][7][8][9][10] VR has now been shown to be effective at reducing pain in settings such as procedural pain (pediatric burn paints, physical therapy), hospitalized patients with pain, and patients with chronic pain. 9,11 Two randomized trials have been performed in obstetric populations: one in laboring women and one in episiotomy repair; both showed promising results.…”
mentioning
confidence: 99%